bahasa inggris SERVANT LEADERSHIP IN THE DEVELOPMENT OF PROFESSIONALISM - Pertiwi, Santhi; Ahmad, Masduki; Suryadi, Suryadi (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research aims to describe professionalism and performance. understand the relationship between service leadership and performance. This research uses a literature study method by observing various kinds of documents from both books and journals. The literature study in this research focuses on researching literature related to servant leadership in professional development. Data collection is carried out by collecting library data, reading, recording and managing research results objectively, systematically, analytically and critically by looking at the year of publication and the most recent research. The results of this research show. Servant leadership can be applied to increase professionalism in the workplace and influence the personality and work motivation of employees